Mean motion resonances among the small satellites of Saturn and Pluto - Santana, Thamiris de (2019)
This work is organized into three parts. In Part I, we present a quick review of Saturn’s satellites Prometheus and Pandora lags problem. We analyzed the lags ratio Q = ∆λpro ∆λpan through the conservation of the angular momentum, that implies the ratio of the lags due to this mutual interaction must be almost constant. However, we found that the values obtained using observational data fit Qobs does not agree with the assumed masses mpan/mpro = 0.56 and is not even nearly constant. It presents a robust linear increasing rate given by Qobs(t) = 0.667 + 0.013t, with t given in years. In this way, we show that only the gravitational interaction between the satellites does not fully explain the lags values. This indicates that a non-mutual mechanism should provoke at least a mean motion changing of 0.45◦/year, also affecting Prometheus or Pandora, contributes to the lag values. In Part II, we performed the astrometry of the satellite Daphnis using the Caviar software in a selected set of images from the ISS-NAC camera of Cassini spacecraft. Daphnis’ astrometry of all Cassini mission period showed that Daphnis had changed its orbit twice. So, we have investigated the stability of Daphnis’ orbit by implemented numerical simulations considering Saturn plus five satellites: Daphnis, Atlas, Prometheus, Pandora, and Mimas and computing the evolution of the Fast Lyapunov Indicator FLI. We showed that Daphnis is on a chaotic orbit with a Lyapunov time of ∼13 years. By investigating possible resonances between Daphnis and other satellites, we found that Prometheus and Atlas with 129:125 and 157:155 mean motion resonant angles, respectively, present some features that could indicate chaos. Additionally, we found that when Prometheus and Atlas are not included in the numerical simulation, Daphnis’ orbit became regular, reinforcing the suggestion that both satellites are playing a role in Daphnis’ chaotic behavior. In Part III, we presented a study of the origin of resonance between the satellites of Pluto. We performed N-body numerical simulations considering the small satellites and Charon evolving under the influence of the tidal force due of Pluto on Charon. Using the J2 effective approach, we showed that the small satellites could be captured into the 3:1, 4:1, 5:1, 6:1 mean motion resonances with Charon. Even for the case of the 5:1 and 6:1 mean motion resonances, it was possible to achieve a capture only when some non-zero eccentricity was added to Charon. Moreover, the 3:1 mean motion resonance between Charon and Styx, in inclination, was the easiest to happen. To find the three body resonance 3:5:2 among Styx, Nix, and Hydra, we looked for two particular resonances among them: 2:1 between Styx and Hydra and 5:4 between Nix and Styx. We have found parameters that allow the capture of the small bodies into the exact two 2-body resonant arguments we need, but not at the same time. In this way, we perceive that we are close to finding the right parameters to represent all the paths of the Pluto’s moons from their past to the current intriguing configuration. Some different ideas may be tested to bring us to the present scenario